CIRCULATING OVARIAN STEROIDS IN RELATION TO SUPEROVULATORY RESPONSE AND EMBRYO RECOVERY IN SAHIWAL COWS AND HEIFERS - SIDDIQUl, M U; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2023)
Relationship between concentrations of circulating ovarian steroids and superovulation (sov.) response and embryo recovery was studied in 12 Sahiwal cattle (6 cows; 6 heifers) treated with FSH·P and PGF2 " given i.m. 48 hr after first FSH injection. On day 7 of first Al, donors were flushed and recovered embryos/ova were graded. Blood plasma samples were analysed for estrogen and progesterone concentrations using RIA. Among 6 cows (Group A), only 3 (50%) responded to sov treatment with 17 CL (5.67/donor) and total 10 embryos were recovered. Mean recovery of total and viable embryos for responded donors and overall were found to be 3.33 and 1. 00 and 1.67 and 0.50 embryos/flush, respectively. All heifers (Group B) responded to sov. treatment with 50 CL (8.33/ donor) and total 37 embryos (18 VE; 16 DE, 2 UFO and 1 zona) were recovered. Mean recovery of total and viable embryos was found to be 6.17 and 3.00 embryos/flush, respectively. Heifers yielded comparatively higher number of mean ovulations (8.33) and embryos, both total (6.17) and viable (3.00), than those of cows (3.17, 1.67 and 0.50, respectively). No significant variation was found in plasma progesterone concentrations among both groups at all sample collection stages. The mean concentrations of plasma estrogen varied significantly between groups. It was found to be significantly (t=3.293, p<0.05) higher at all stages for heifers than cows. Mean progesterone and estrogen concentrations at synchronized estrus (0.42+0.17 ng/ml and 18.50+ 7.55 pg/ml, respectively) and at PGF2" injection during FSH treatment (1.85+0. 76 ng/ml and 12.67+5.17 pg/ml, respectively) in heifers were found to be correlated significantly with 8.33 ovulations/donor (R2=0.902, p<0.031; R2=0.831, p<0.069, respectively). Estrogen concentrations remained highest at superovulatory estrus in cows (39.33+16.06) and at synchronized estrus following PGF2 ... II injection in heifers (18.50+7.55 pg/ml). Mean progesterone concentration declined significantly between PGF2(l injection during FSH treatment and on the day of superovulatory estrus in heifers (2.11 +0.86 to 0.25+0.10 ng/ml) and cows (1.85+0. 76 to 0. 73+0.30 ng/rnl). The mean estrogen concentrations were significantly higher at all stages in heifers than cows and mean concentrations of progesterone and estrogen at synchronized estrus and at the time of PGF2u injection during FSH treatment in heifers were correlated significantly with ovulation rate. It was concluded that better sov. response and embryo recovery in heifers were related with the better profile of ovarian steroids.